Pengaruh Beban Kerja dan Job Insecurity terhadap Turnover Intention melalui Kepuasan Kerja : Studi Kasus pada PT Java Wood Industri - Musfirotul Ainiyah; Bayu Kurniawan; Noventia Karina Putri (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of workload and job insecurity on turnover intention through job satisfaction as a mediating variable at PT Java Wood Industri. The research uses a quantitative explanatory approach with a sample of 303 employees selected through proportional random sampling. Data were collected using a questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS 26. The results show that workload has a significant positive effect on turnover intention, while job insecurity does not significantly affect turnover intention. Job satisfaction also has a significant positive effect on turnover intention. However, neither workload nor job insecurity significantly affects job satisfaction, and job satisfaction does not mediate the relationship between workload/job insecurity and turnover intention. The findings suggest that companies should focus on managing workload and improving job satisfaction to reduce employee turnover intention.